Magnetic irreversibility in VO2/Ni bilayers. (28th August 2018) - Lauzier, J; Sutton, L; de la Venta, J
Abstract: We studied the temperature dependence of the magnetic properties of VO2 /Ni bilayers. The Ni films were deposited on either monoclinic or rutile phase VO2 . The temperature induced VO2 transformation from a monoclinic to a rutile structure induces strain in the Ni film. Due to an inverse magnetoelastic effect the coercivity of the Ni films is strongly modified. Both Ni films show strong enhancement of the coercivity near the transition temperature. The coercivity enhancement of Ni is associated with the phase coexistence observed in the VO2 first order phase transition. Above the transition temperature, Ni deposited on monoclinic VO2 shows a coercivity enhancement whereas Ni deposited on rutile VO2 shows suppression of the coercivity. The samples were cycled several times to check if the changes in coercivity were reversible. While samples with Ni deposited on rutile VO2 show reversibility, samples with Ni deposited on monoclinic VO2 shown an irreversibility after the first structural phase transition. This irreversibility can be associated with cracking of the VO2 layer as it relieves stress due to the transition and has implications for the resistance versus temperature behavior of the VO2 .